Acute rule-out of non-ST-segment elevation acute coronary syndrome in the (pre)hospital setting by HEART score assessment and a single point-of-care troponin: rationale and design of the ARTICA randomised trial - Aarts, Goaris W A; Camaro, Cyril; van Geuns, Robert-Jan; Cramer, Etienne; van Kimmenade, Roland R J; Damman, P; van Grunsven, Pierre M; Adang, Eddy; Giesen, Paul; Rutten, Martijn; Ouwendijk, Olaf; Gomes, Marc E R; et al. (BMJ Open, 2020)
Introduction Because of the lack of prehospital protocols to rule out a non-ST-segment elevation acute coronary syndrome (NSTE-ACS), patients with chest pain are often transferred to the emergency department (ED) for thorough evaluation. However, in low-risk patients, an ACS is rarely found, resulting in unnecessary healthcare consumption. Using the HEART (History, ECG, Age, Risk factors and Troponin) score, low-risk patients are easily identified. When a point-of-care (POC) troponin measurement is included in the HEART score, an ACS can adequately be ruled out in low-risk patients in the prehospital setting. However, it remains unclear whether a prehospital rule-out strategy using the HEART score and a POC troponin measurement in patients with suspected NSTE-ACS is cost-effective. Methods and analysis The ARTICA trial is a randomised trial in which the primary objective is to investigate the cost-effectiveness after 30 days of an early rule-out strategy for low-risk patients suspected of a NSTE-ACS, using a modified HEART score including a POC troponin T measurement. Patients are included by ambulance paramedics and 1:1 randomised for (1) presentation at the ED (control group) or (2) POC troponin T measurement (intervention group) and transfer of the care to the general practitioner in case of a low troponin T value. In total, 866 patients will be included. Follow-up will be performed after 30 days, 6 months and 12 months. Ethics and dissemination This trial has been accepted by the Medical Research Ethics Committee region Arnhem-Nijmegen. The results of this trial will be disseminated in one main paper and in additional papers with subgroup analyses. Trial registration number Netherlands Trial Register (NL7148).